1988
DOI: 10.1111/j.1365-3083.1988.tb01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD43 Expression during Activation and Terminal Differentiation of Human B Cells

Abstract: Only a small population (25-30%) of human peripheral blood B lymphocytes expresses large sialoglycoprotein (LSGP) (CD43). However, in the presence of autologous T cells and pokeweed mitogen (PWM) a majority (50-90%) of the immunoglobulin-producing cells (cIg+ cells) that develop from these B cells express CD43 is detected with anti-CD43 monoclonal antibodies (MoAb) B1B6, and the proportion of CD43+cIg+ cells increases with time of culture. Furthermore, a relatively larger proportion (60-80%) of the IgG-produci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…In humans, both CD45 and CD43 are considered as pan-hematopoietic markers, 26,27 though CD45 is not expressed on platelets and cells of the erythroid lineage, 27 whereas CD43 is expressed on platelets and erythroid progenitors, but it is not detected on mature erythrocytes and B-cell subsets. 26,28 CD41a and CD235a are known markers of megakaryocytic and erythroid cell lineages, respectively. 29,30 Using PCR and flow cytometry, we found that undifferentiated hESCs did not express CD235a and CD45 mRNA ( Figure 1A) or protein (not shown).…”
Section: Cd43 Is the Earliest And Predominant Pan-hematopoietic Markementioning
confidence: 99%
“…In humans, both CD45 and CD43 are considered as pan-hematopoietic markers, 26,27 though CD45 is not expressed on platelets and cells of the erythroid lineage, 27 whereas CD43 is expressed on platelets and erythroid progenitors, but it is not detected on mature erythrocytes and B-cell subsets. 26,28 CD41a and CD235a are known markers of megakaryocytic and erythroid cell lineages, respectively. 29,30 Using PCR and flow cytometry, we found that undifferentiated hESCs did not express CD235a and CD45 mRNA ( Figure 1A) or protein (not shown).…”
Section: Cd43 Is the Earliest And Predominant Pan-hematopoietic Markementioning
confidence: 99%
“…B cells were purified as previously described (31,32). In short, T cells were removed by two cycles of rosetting with neuraminidasetreated sheep erythrocytes.…”
Section: Coisolation Of Fdcs With In Vivo Activated B Lymphocytesmentioning
confidence: 99%
“…B cells demonstrate a unique developmental program for mCD43 expression that makes them particularly amenable for the in vivo manipulation of mCD43 within a physiologically relevant context. CD43 is present on the surface of early B-cell progenitors and on terminally differentiated plasma cells but is absent on mature B cells (24)(25)(26)(27)(28)(29)(30). We took advantage of this "ON-OFF-ON" expression pattern of mCD43 in the B-cell lineage and altered its temporal expression in transgenic (TG) mice by using the immunoglobulin heavy chain enhancer to drive mCD43 expression in mature B cells (31).…”
mentioning
confidence: 99%
“…1). The hybrid construct was microinjected into fertilized mouse eggs, implanted into pseudopregnant females, and allowed to develop to term (36 (24,(26)(27)(28)(29)(30). In the three TG lines examined, however, >95% of B220+ B cells expressed mCD43, as indicated by the large double-positive population (Fig.…”
mentioning
confidence: 99%